2013
DOI: 10.1111/tbed.12073
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiaeInfection in Domestic Rabbits,Oryctolagus cuniculus

Abstract: Streptococcus agalactiae (Group B streptococcus, GBS) has emerged as an important pathogen that affects humans and animals, including aquatic species. In August 2011, a severe infectious disease affecting rabbits, which caused 42% mortality, occurred in Mianyang, Sichuan Province, China. The main clinical signs included acute respiratory distress syndrome, fever, paddling and convulsions. A Gram-positive, chain-forming coccus was isolated from the primary organs and tissues of diseased rabbits and then identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…FFC also shows activity against many chloramphenicol-resistant bacterial strains involved in common infections in most animals [ 4 , 7 ]. Recent studies have indicated that FFC can effectively inhibit the growth of Streptococcus agalactiae , an important pathogen resulting in a severe infectious disease in domestic rabbits that is resistant to penicillin, amoxicillin, and tetracycline [ 27 ]. The pharmacokinetics of FFC have been extensively studied in many species of animals [ 25 ], especially in rabbits [ 1 , 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…FFC also shows activity against many chloramphenicol-resistant bacterial strains involved in common infections in most animals [ 4 , 7 ]. Recent studies have indicated that FFC can effectively inhibit the growth of Streptococcus agalactiae , an important pathogen resulting in a severe infectious disease in domestic rabbits that is resistant to penicillin, amoxicillin, and tetracycline [ 27 ]. The pharmacokinetics of FFC have been extensively studied in many species of animals [ 25 ], especially in rabbits [ 1 , 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possible routes of infection and transmission for S. agalactiae infection in rays may include horizontal infection, through waterborne exposure or oral transmission through ingestion of contaminated feed, as documented for fish and other animals (Bowater, ; Delamare‐Deboutteville et al., ; Hetzel et al., ; Ren et al., ). In the present study, some rays had inflammation and S. agalactiae infection in the soft tissues of the dorsal cranium, suggestive of involvement of endolymphatic ducts, which bacteria could ascend to infect the brain and meninges.…”
Section: Discussionmentioning
confidence: 99%
“…In general, S. agalactiae infection in fish typically results in lesions indicative of bacteraemia, that is, disseminated multifocal and multi‐organ foci of inflammation, especially involving brain, eye, heart, kidney, liver and spleen (Baya et al., ; Bowater et al., ; Evans, Klesius et al., ; Hernández et al., ). However, the nature of the inflammatory response varies amongst host species, ranging from granulomatous, to mononuclear, to granulocytic or necrotizing (Edelsten & Pegram, ; Liu et al., ; Musa et al., ; Ren et al., ; Zappulli et al., ). Rays in the present study showed a mixture of granulocytic to mononuclear inflammatory lesions, consistent with pathology shown by juvenile Queensland grouper inoculated with S. agalactiae (Bowater, ; Delamare‐Deboutteville et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus agalactiae, or group B Streptococcus (GBS), is a Gram positive coccus with global distribution (1,2). Streptococcus agalactiae cause neonatal meningitis in humans, mastitis in cattle, acute sepsis in rabbits, and meningoencephalitis as well as septicemia in fish (2)(3)(4). The capsular polysaccharide is contributing to the pathogenicity of S. agalactiae and it is useful in bacterial genotyping (5).…”
Section: Introductionmentioning
confidence: 99%